Diversidade, biogeografia e conservação das Begoniaceae no Estado do Espírito Santo, Brasil. - Kollmann, Ludovic Jean Charles (2012)
Begoniaceae is represented by the genus Begonia in Brazil with approximately 215 species found mainly in the Atlantic Forest in all forest physiognomies exeter in mangrove. The Espírito Santo state remaining approximately 11% of original vegetation consisted of fragments of different sizes where the most part of the richness and diversity of capixaba biota is finding. The aims of this study were listing the records of the Begonia species in the state of Espírito Santo, characterize the vegetation where they occur, the geographical distribution patterns, richness, diversity, endemism, compare their distribution with the Conservation Units of Integral Protection and areas listed as priorities for Biodiversity Conservation in Espírito Santo, set the status of conservation of species and infer similarity of the Begonia species of the Espírito santo state with the other states of Brazil. The methodology used is the most commonly used in floristic survey and taxonomy of phanerogams, literature, analysis of herbarium specimens and natural populations. In Espírito Santo state were found 53 species of Begonia, including four new species, three taxa were synonymized and one rehabilitated. Of these 53 species, 42 occur in ombrofilous forest, four in semi deciduous forest and four simultaneously in the two vegetation types. Three species occure in the Neotropics, three are endemic to South America, two occure in Brazil extra-Amazonian, 45 are endemic to the Atlantic Forest and 18 are endemic to the Espirito Santo state, included two considered microendémicas. Using the IUCN criteria, 11 species are considered Critically Endangered, nine Endangered, five Vulnerabel and two Extinct in the Wild. The highest concentration of species was observed in the mountain region. The highest richness and diversity were observed in the municipality of Santa Teresa, Santa Leopoldina, Cariacica, Vargem Alta and Castelo. The similarity analysis showed that the species of Begonia in the Espírito Santo have more similarity with Minas Gerais and later Rio de Janeiro, Sao Paulo and Bahia states. Are still provided, identification key, descriptions, distribution, habitat, etymology, comments, maps and illustrations.